Effect of Co-transfection of Anti-myostatin shRNA Constructs in Caprine Fetal Fibroblast Cells. Issue 1 (2nd January 2016) - Hati Boruah, Jyoti Lakshmi; Ranjan, Rakesh; Gogoi, Hamen; Pandey, Saurabh Kumar; Kumar, Dharmendra; Phukan, Amlan Jyoti; Bori, Joygeswar; Sarkhel, Bikash Chandra
ABSTRACT: Knockdown of myostatin gene (MSTN), transforming growth factor-β superfamily, and a negative regulator of the skeletal muscle growth, by RNA interference (RNAi), has been reported to increase muscle mass in mammals. The current study was aimed to cotransfect two anti-MSTN short hairpin RNA (shRNA) constructs in caprine fetal fibroblast cells for transient silencing of MSTN gene. In the present investigation, approximately 89% MSTN silencing was achieved in transiently transfected caprine fetal fibroblast cells by cotransfection of two best out of four anti-MSTN shRNA constructs. Simultaneously, we also monitored the induction of IFN responsive genes (IFN), pro-apoptotic gene (caspase3) and anti-apoptotic gene (MCL-1) due to cotransfection of different anti-MSTN shRNA constructs. We observed induction of 0.66-19.12, 1.04-4.14, 0.50-3.43, and 0.42-1.98 for folds IFN-β, OAS1, caspase3, and MCL-1 genes, respectively (p < 0.05). This RNAi based cotransfection method could provide an alternative strategy of gene knockout and develop stable caprine fetal fibroblast cells. Furthermore, these stable cells can be used as a cell donor for the development of transgenic cloned embryos by somatic cell nuclear transfer (SCNT) technique.